A comparative study for optimizing photocatalytic activity of TiO2-based composites with ZrO2, ZnO, Ta2O5, SnO, Fe2O3, and CuO additives - I. Abdelfattah; A. M. El-Shamy (Scientific Reports, 2024)
Abstract Despite the widespread use of titanium dioxide (TiO2) in photocatalytic applications, its inherent limitations, such as low efficiency under visible light and rapid recombination of electron-hole pairs, hinder its effectiveness in environmental remediation. This study presents a comparative investigation of TiO2-based composites, including TiO2/ZrO2, ZnO, Ta2O3, SnO, Fe2O3, and CuO, aiming to assess their potential for enhancing photocatalytic applications. Photocatalysis holds promise in environmental remediation, water purification, and energy conversion, with TiO2 being a prominent photocatalyst. To improve efficiency and broaden applicability, various metal oxide composites have been explored. Composites were synthesized and characterized using techniques such as XRD, SEM, TEM, and zeta potential analysis to evaluate their structural and morphological properties. Photocatalytic performance was assessed by degrading herbicide Imazapyr under UV illumination. Results revealed that, the photo-activity of all prepared composites were more effective than the photo-activity of commercial hombikat UV-100. The photonic-efficiency is arranged according to the order TiO2/CuO > TiO2/SnO > TiO2/ZnO > TiO2/Ta2O3 > TiO2/ZrO2 > TiO2/Fe2O3 > Hombikat TiO2-UV100. All composites exhibited superior performance, attributed to enhanced light absorption and charge separation. The study underscores the potential of these composites for environmental remediation and energy conservation, offering valuable insights for the development of advanced photocatalysts.